Rod-Mediated Dark Adaptation and Macular Pigment Optical Density in Older Adults with Normal Maculas. (3rd July 2018) - Zarubina, Anna V.; Huisingh, Carrie E.; Clark, Mark E.; Sloan, Kenneth R.; McGwin, Gerald; Crosson, Jason N.; Curcio, Christine A.; Owsley, Cynthia
ABSTRACT: Purpose : To examine the association between macular pigment optical density (MPOD) and rod-mediated dark adaptation (RMDA) in persons ≥60 years old with normal maculas as determined by an accepted color fundus photography grading system. Methods : This cross-sectional analysis used baseline data from eyes in the Alabama Study on Early Age-Related Macular Degeneration. Eyes at step 1 in the AREDS 9-step grading system were considered normal. Eyes were additionally assessed by spectral domain optical coherence tomography (SD-OCT). Foveal MPOD was estimated via heterochromatic flicker photometry, and RMDA was assessed with a computerized dark adaptometer. The association between RMDA and MPOD was examined via Spearman correlation coefficients adjusted for age. Results : In 306 eyes from 306 persons (mean age 68.2 years) in normal macular health, MPOD was not associated with RMDA (age-adjusted rank correlation = 0.043, p = 0.45). After 81 eyes with incidental macular findings by SD-OCT evaluation were excluded, the association between MPOD and RMDA remained null ( N = 225, age-adjusted r = 0.015, p = 0.82). Conclusion : In a large sample of normal aged eyes, RMDA, a visual function that is rate limited by retinoid availability to photoreceptors across the complex of retinal pigment epithelium, Bruch's membrane, and choriocapillaris, is not related to MPOD in the neurosensory retina.